Estimating Child Mortality Rate and its Trend in Hamadan Province, Western Iran from 1990 to 2016: Implications for Sustainable Development Goal - Mohammadi, Younes (J Res Health Sci, 2018)
Background: Child mortality is one of the major health indices and the main targets in sustainable development goals. This study aimed to estimate child mortality rate and assess the progress toward sustainable development goals in Hamadan Province, western Iran and its districts from 1990 to 2016. Study design: A cross-sectional study. Methods: We used two data sources including death registration system (DRS) and summary birth history data (SBH) of 2010 census for estimating child mortality rate. SBH data was analyzed by Maternal Age Cohort and Maternal age period methods. To obtain the final trend with 95% uncertainty, we used Bayesian Penalized B-Spline. Results: At provincial level, child mortality rate reduced by 82% from 1990 (97 per 1000 live births) to 2016 (16 per 1000 live births). At district level, in 2016, the highest child mortality rate belonged to Toyserkan and Kaboodarahang districts with 18 per 1000 live births, and the lowest child mortality rate belonged to Hamadan and Razan districts with 12 per 1000 live births. The highest and the lowest reduction rate from 1990 to 2016 belonged to Razan and Kaboodarahang districts, respectively. Conclusions: The rate of child mortality has declined massively at both provincial and district levels. However, disparity existed among districts of Hamadan Province. The level of maternal education and income level was associated with disparity.